1999
DOI: 10.1111/j.1469-7793.1999.041ad.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐linked glycosylation sites determine HERG channel surface membrane expression

Abstract: Long QT syndrome (LQT) is an electrophysiological disorder that can lead to sudden death from cardiac arrhythmias. One form of LQT has been attributed to mutations in the human ether‐a‐go‐go‐related gene (HERG) that encodes a voltage‐gated cardiac K+ channel. While a recent report indicates that LQT in some patients is associated with a mutation of HERG at a consensus extracellular N‐linked glycosylation site (N629), earlier studies failed to identify a role for N‐linked glycosylation in the functional express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
117
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(122 citation statements)
references
References 25 publications
3
117
2
Order By: Relevance
“…One type of hereditary AQP2 mutant (T125M), which causes recessive nephrogenic diabetes insipidus, is not glycosylated because the N-linked glycosylation motif is disrupted (29). Glycosylation has also been shown to be essential for the efficient function and surface expression of the NaCl cotransporter (14), the cardiac potassium channel HERG (30), and the Oatp1 organic anion transporter (16). We have previously shown that AVP and FSK can stimulate urea flux in MDCK cells stably expressing UT-A1 (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…One type of hereditary AQP2 mutant (T125M), which causes recessive nephrogenic diabetes insipidus, is not glycosylated because the N-linked glycosylation motif is disrupted (29). Glycosylation has also been shown to be essential for the efficient function and surface expression of the NaCl cotransporter (14), the cardiac potassium channel HERG (30), and the Oatp1 organic anion transporter (16). We have previously shown that AVP and FSK can stimulate urea flux in MDCK cells stably expressing UT-A1 (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Glycosylation of ion channels has been shown to affect the intracellular transport, cell membrane targeting/stability, and activity of ion channels (16,18,19,(21)(22)(23). For example, the gating properties of a neuronal Na ϩ channel change as the glycosyl moiety of the channel protein changes during development (21).…”
Section: Discussionmentioning
confidence: 99%
“…Glycosylation site mutant channels, although properly folded and assembled, are degraded through cytoplasmic proteasomes (22). Similarly, N-linked glycosylation of the HERG channel is required for its cell surface expression (23).…”
mentioning
confidence: 99%
“…18). Briefly, cells were placed on the stage of an inverted microscope (Zeiss IM35) at room temperature.…”
Section: Methodsmentioning
confidence: 99%